Immune monitoring facilitates the clinical decision in multifocal COVID-19 of a pancreas-kidney transplant patient - Babel, Nina; Anft, Moritz; Blazquez-Navarro, Arturo; Doevelaar, Adrian A.N.; Seibert, Felix S.; Bauer, Frederic; Rohn, Benjamin J.; Hoelzer, Bodo; Thieme, Constantin J.; Roch, Toralf; Meister, Toni L.; Pfaender, Stephanie; et al. (American Journal of Transplantation, 2020)
The optimal management in transplant recipients with coronavirus disease 2019 (COVID-19) remains uncertain. The main concern is the ability of immunosuppressed patients to generate sufficient immunity for antiviral protection. Here, we report on immune monitoring facilitating a successful outcome of severe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-associated pneumonia, meningoencephalitis, gastroenteritis, and acute kidney and pancreas graft failure in a pancreas-kidney transplant recipient. Despite the very low numbers of circulating B, NK, and T cells identified in follow-up, a strong SARS-CoV-2 reactive T cell response was observed. Importantly, we detected T cells reactive to Spike, Membrane, and Nucleocapsid proteins of SARS-CoV-2 with majority of T cells showing polyfunctional proinflammatory Th1 phenotype at all analyzed time points. Antibodies against Spike protein were also detected with increasing titers in follow-up. Neutralization tests confirmed their antiviral protection. A correlation between cellular and humoral immunity was observed underscoring the specificity of demonstrated data. We conclude that analyzing the kinetics of nonspecific and SARS-CoV-2-reactive cellular and humoral immunity can facilitate the clinical decision on immunosuppression adjustment and allow successful outcome as demonstrated in the current clinical case. Although the antiviral protection of the detected SARS-CoV-2-reactive T cells requires further evaluation, our data prove an ability mounting a strong SARS-CoV-2-reactive T cell response with functional capacity in immunosuppressed patients.
CRIS-Team Scopus Importer:2020-09-18